(untitled) (Baghdad Science Journal, 2022)
The efficiency of attapulgite liners as anti-seepage for crude oil is examined. Consideration is given to the potential use of raw attapulgite and mixture attapulgite with prairie hay and coconut husk as liners to prevent crude oil seepage. Attapulgite clay used in this study was brought from Injana formation /Western Desert of Iraq. Two types of Crude oil brought from Iraqi oil fields were used in experiments; heavy crude oil from East-Baghdad oil field and light crude oil from Nassiriya oil field. Initially the basic properties of attapulgite and crude oils were determined. The attapulgite clay was subjected to mineralogical, chemical and scanning electron microscope analyses. Raw Attapulgite 150µm, 75µm, and 53µm were tested as anti-seepage liners for heavy and light crude oil. Experiments showed that raw attapulgite liners 53µm and 75µm are good in terms of retention and prevention of seepage so they can be used as the main layer to impede the flow of heavy crude oil. Raw attapulgite150µm could not be used as a liner to impede the flow of crude oil. This type of liner is totally inefficient for heavy and light crude oil. Adding prairie hay to attapulgite 150µm gives a good barrier medium that retains heavy crude oil and prevents it from seepage as long as possible. Raw attapulgite liners failed to prevent light crude oil seepage whereas the partial substitution of attapulgite by prairie hay or coconut enhanced the performance of the liner. Moreover, the addition of prairie hay with coconut to attapulgite enhanced the performance of the liner to a greater extent compared to raw attapulgite liners and mixture liner attapulgite with prairie hay.